Ökumenische Eschatologie? Kontroverstheologische Analysen zur GER nach 25 Jahren. - Thiede, Werner (Theologische Beiträge, 2024)
Why, even after a quarter of a century, has the "Joint Declaration on the Doctrine of Justification" (JDDE) not led to any major progress in bilateral relations between the two major denominations ? Obviously, there has only been consensus on some of the so-called "fundamental truths" of the doctrine of justification. In particular, the eschatological tip of the New Testament doctrine of justification (e. g John 5:34), which had become essential for Reformation theology, has been left out. Some ecumenical convergences in the field of eschatology since the second half of the 20th century cannot hide the remaining differences in the basic understanding of the grace of justification.
CRIS-Team Scopus Importer:2024-12-06